1999
DOI: 10.1243/0954405991516732
|View full text |Cite
|
Sign up to set email alerts
|

Improving wood surface form by modification of the rotary machining process—a mechatronic approach

Abstract: Rotary machining is extensively used for planing and moulding operations within the woodworking industry. Although the surface form produced by this machining method is acceptable, the rotary machining action produces cutter marks on the wood surface so that further finishing operations, such as sanding, are often required to generate a product of acceptable standard. It has been theorized that the surface finish of planed and moulded timber products may be improved by oscillation of the cutter block in either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In the first approach, models that predict the quantitative relationships between machining parameters (cutting speed and feed speed) and surface finish quality are used to select optimal machining parameters for obtaining a high quality surface finish. 6,7 In the second approach, surface finish quality is improved through real-time modification of process kinematics (cutter-path optimisation) [8][9][10][11][12] and active vibration control. 13 This first approach has been used to minimise surface roughness during milling of medium density fibreboard (MDF) in Gaitonde et al 6 and Davim et al 7 It is reported in both articles that the surface finish quality of milled MDF increases with an increase in cutting speed.…”
Section: Review Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first approach, models that predict the quantitative relationships between machining parameters (cutting speed and feed speed) and surface finish quality are used to select optimal machining parameters for obtaining a high quality surface finish. 6,7 In the second approach, surface finish quality is improved through real-time modification of process kinematics (cutter-path optimisation) [8][9][10][11][12] and active vibration control. 13 This first approach has been used to minimise surface roughness during milling of medium density fibreboard (MDF) in Gaitonde et al 6 and Davim et al 7 It is reported in both articles that the surface finish quality of milled MDF increases with an increase in cutting speed.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…The first one is the introduction of additional horizontal cutterhead movement during the machining process. [8][9][10] The objective of the horizontal cutterhead movement introduction is to produce a surface finish with reduced waviness heights.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…The need for a generalized model for surface defect simulation was identi®ed. Recent work [25,29] has established and re®ned such a model environment currently implemented via MATLab TM [30].…”
Section: Modelling Of Surface Defectsmentioning
confidence: 99%
“…The resultant surface is computed as a series of discrete points. A few authors [1,7,8] developed surface simulation algorithms specifically for wood machining. These algorithms only take into account the rotary machining process kinematics.…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…without increasing the number of knives or without increasing the cutterhead diameter) if the modified cutterhead movement is synchronized with the rotational position of the knives. For example, horizontal cutterhead movement, investigated in reference [1], reduces waviness height when synchronized with the position of the knives. This paper investigates the influence of vertical cutterhead movement.…”
mentioning
confidence: 99%